1997
DOI: 10.1046/j.1469-8137.1997.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil compaction on plant growth phosphorus uptake and morphological characteristics of vesicular—arbuscular mycorrhizal colonization of Trifolium subterraneum

Abstract: SUMMARYWe investigated the effect of soil compaction and phosphorus (P) application on morphological characteristics of mycorrhizal colonization and growth responses, to determine the reasons for reduced responses observed in our previous work with compacted soil. Growth, phosphorus (P) uptake and intensity of vesicular-arbuscular (VA) mycorrhizal colonization were studied in clover plants {Trifolium subterraneuvi L.) witli and without VA mycorrhizal colonization at two P applications and three levels of soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 29 publications
0
33
0
2
Order By: Relevance
“…In addition, the role of arbuscules have not been fully confirmed, and other exchange sites-including coiling AMF-are possible (Brundrett 2004;Brundrett 2009). Total root length colonized by AMF, either on a per-plant or per-ground area basis, has also been used (e.g., Nadian et al 1997;Allen 2001). This index may be a closer estimate of AMF abundance within a plant or ecosystem, respectively.…”
Section: How Are Arbuscular Mycorrhizal Fungi Assessed?mentioning
confidence: 99%
“…In addition, the role of arbuscules have not been fully confirmed, and other exchange sites-including coiling AMF-are possible (Brundrett 2004;Brundrett 2009). Total root length colonized by AMF, either on a per-plant or per-ground area basis, has also been used (e.g., Nadian et al 1997;Allen 2001). This index may be a closer estimate of AMF abundance within a plant or ecosystem, respectively.…”
Section: How Are Arbuscular Mycorrhizal Fungi Assessed?mentioning
confidence: 99%
“…City Beach in compacted soil can be attributed to the combined effects of decreased total root length and root length colonized. Our previous results obtained with G. intraradices (Nadian et al, 1997) indicated that soil compaction to a bulk density of 1n60 Mg m −$ had no effect on the fraction of root length containing arbuscules and vesicles, but total root length colonized by arbuscules, vesicles or by any combination of arbuscules, vesicles and intraradical hyphae significantly decreased. The simplest explanation for the data from fatty acid analysis presented here is that the biomass of mycorrhizal fungi (presumably including the external hyphae and spores) also declines as soil compaction increases.…”
Section: mentioning
confidence: 99%
“…Before compacting the soil, P fertilizer (as NaH # PO % ) was mixed throughout the sieved soil at a rate that would give 15 mg P dm −$ soil after compaction (Nadian et al, 1997). In our previous work (Nadian et al, 1996), the greatest mycorrhizal growth response of Trifolium subterraneum to Glomus intraradices was achieved when the soil was supplied with 15 mg P dm −$ ; this level of P was therefore used in the present study.…”
Section: Phosphate Applicationmentioning
confidence: 99%
See 2 more Smart Citations